POLITIK HUKUM KEIMIGRASIAN INDONESIA: STUDI PENDEKATAN SEJARAH DAN KONTEMPORER - M Alvi Syahrin (SOL JUSTICIA, 2019)
Paradigms or perspectives on immigration issues are not limited to population movements between countries which are only seen from the element of movement but also include all aspects that accompany them both regionally and globally. A holistic understanding of the immigration paradigm and its changes causes the arrangement of immigration law to be carried out in a direct manner which is a political elaboration of national immigration law and becomes more appropriate. The political development of immigration law in Indonesia is divided into two parts, namely (1) Politics of the National Immigration Law which consists of: Legal Politics in the Field of Immigration during the Dutch East Indies (1913-1949), Legal Politics in Immigration in 1950-1992, Politics Law on Immigration in 1992-2011, Legal Policy in Immigration in 2011 - Now. With the issuance of Law No. 6 of 2011 concerning Immigration which was promulgated on May 5, 2011, then based on Chapter XV Article 142, Law No. 9 of 1992 concerning Immigration and its related provisions are declared null and void. When compared, the material of Law No. 6 of 2011 concerning Immigration, basically does not substantially change the politics of immigration law in principle which is contained in the previous immigration law. (2) Politics of International Immigration Law. The development of legal politics in the field of immigration globally has undergone many changes, which if we look at the post-World War II period, in order to accommodate and accommodate the problems that arise as a result of large-scale exodus (exodus), especially the state- countries directly involved in World War II. Problems faced globally at that time both concerning the country of origin, transit country and destination country have different problems that can be categorized in several ways, such as poverty, income level per capita, quality of education, age, culture, race, religion, and several other problems.